The Effect of Pain Neuroscience Education in the Treatment of Fibromyalgia: A Narrative Review - H Shrinidhi Hebbar; Ruchita Harish Narsia (Journal of Clinical and Diagnostic Research)
Pain Neuroscience Education (PNE) is a widely used approach for educating patients with chronic musculoskeletal conditions. It has shown significant improvements in pain levels, disability and psychosocial outcomes, particularly when combined with exercise and manual therapy. Several studies have emphasised the effectiveness of PNE in reducing pain and enhancing the quality of life in individuals with Fibromyalgia (FM). This literature review aimed to systematically assess the effectiveness of PNE in individuals with FM. A comprehensive literature search was conducted using electronic databases, including Google Scholar, PubMed, ResearchGate and ScienceDirect, to identify studies examining the impact of PNE on FM. The review concluded that PNE alone did not significantly benefit patients with FM. However, when integrated with other group interventions, such as physical therapy or exercise therapy, PNE was more effective in reducing the impact of psychosocial variables and pain intensity compared to either treatment alone.